The importance of hiring frictions in business cycles - Renato Faccini; Eran Yashiv (Quantitative Economics, 2022)
Hiring is a costly activity reflecting firms' investment in their workers. Microdata show that hiring costs involve production disruption. Thus, cyclical fluctuations in the value of output, induced by price frictions, have consequences for the optimal allocation of hiring activities. We outline a mechanism based on cyclical markup fluctuations, placing emphasis on hiring frictions interacting with price frictions. This mechanism generates strong propagation and amplification of all key macroeconomic variables in response to technology shocks and mutes the traditional transmission of monetary policy shocks. A local projection analysis of aggregate U.S. data shows that the empirical results, including the cyclicality of markups, are consistent with the model's impulse response functions.
Keywords: E22; E24; E32; E52; 330; Business cycles; propagation and amplification; markup cyclicality; hiring as investment; intertemporal allocation; confluence of hiring and price frictions